Ouabain binding, ATP hydrolysis, and Na+,K(+)-pump activity during chemical modification of brain and muscle Na+,K(+)-ATPase - Teisinger, J; Zemková, H; Svoboda, P; Amler, E; Vyskocil, F (Journal of neurochemistry, 1992)
The effects of 16 group-specific, amino acid-modifying agents were tested on ouabain binding, catalytical activity of membrane-bound (rat brain microsomal), sodium dodecyl sulfate-treated Na+,K(+)-ATPase, and Na+,K(+)-pump activity in intact muscle cells. With few exceptions, the potency of various tryptophan, tyrosine, histidine, amino, and carboxy group-oriented drugs to suppress ouabain binding and Na+,K(+)-ATPase activity correlated with inhibition of the Na+,K(+)-pump electrogenic effect. ATP hydrolysis was more sensitive to inhibition elicited by chemical modification than ouabain binding (membrane-bound or isolated enzyme) and than Na+,K(+)-pump activity. The efficiency of various drugs belonging to the same "specificity" group differed markedly. Tyrosine-oriented tetranitromethane was the only reagent that interfered directly with the cardiac receptor binding site as its inhibition of ouabain binding was completely protected by ouabagenin preincubation. The inhibition elicited by all other reagents was not, or only partially, protected by ouabagenin. It is surprising that agents like diethyl pyrocarbonate (histidine groups) or butanedione (arginine groups), whose action should be oriented to amino acids not involved in the putative ouabain binding site (represented by the -Glu-Tyr-Thr-Trp-Leu-Glu- sequence), are equally effective as agents acting on amino acids present directly in the ouabain binding site. These results support the proposal of long-distance regulation of Na+,K(+)-ATPase active sites.
Keywords: Electrophysiology; Rats; elektrofyziologie; mozek; sodíko-draslíková ATPasa; Muscles; ouabain; krysa rodu Rattus; Ouabain; Brain; zvířata; adenosintrifosfát; svaly; Hydrolysis; Sodium-Potassium-Exchanging ATPase; hydrolýza; aminokyseliny; Adenosine Triphosphate; Amino Acids; Animals